2016
DOI: 10.1002/ps.4277
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prediction of black rot epidemics in vineyards using a weather-driven disease model

Abstract: The model was highly accurate and robust in predicting the infection periods and dynamics of black rot epidemics. The model can be used for scheduling fungicide sprays in vineyards. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Rossi et al (2014) and Onesti et al (2016) indicated that the weather conditions were less conducive for the disease in 2012 and 2013 than in 2014. Although the amount of mummies used each year was the same (20 g per spore sampler), the mummies may have differed in their level of G. bidwellii colonisation and in the stromata-bearing pycnidia and ascomata, depending on bunch disease severity and weather conditions in the vineyards where the mummies were collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rossi et al (2014) and Onesti et al (2016) indicated that the weather conditions were less conducive for the disease in 2012 and 2013 than in 2014. Although the amount of mummies used each year was the same (20 g per spore sampler), the mummies may have differed in their level of G. bidwellii colonisation and in the stromata-bearing pycnidia and ascomata, depending on bunch disease severity and weather conditions in the vineyards where the mummies were collected.…”
Section: Discussionmentioning
confidence: 99%
“…The mummies used as the inoculum source each year were obtained from one composite batch of mummies that was collected that year from different vineyards and areas affected by black rot; precise information about black rot severity on bunches in those vineyards was not available. Rossi et al (2014) and Onesti et al (2016) indicated that the weather conditions were less conducive for the disease in 2012 and 2013 than in 2014. Therefore, mummies used in 2015 (which would have been infected in 2014) may have produced more ascomata and pycnidia than those used in 2013 and 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The disease severities observed in the four epidemics mentioned in the previous section (AK-96, CL-12, CL-13, and CL-14; Table 2) were compared to the accumulated infection severities predicted by the model by using linear regression analysis. To make the data comparable [75,76], we rescaled (from 0 to 1) each infection severity value to the disease severity observed in each epidemic at harvest. The goodness-of-fit of observed vs. predicted data was estimated by determining the root mean square error (RMSE), the coefficient of residual mass (CRM), and the concordance correlation coefficient (CCC) [77,78].…”
Section: Prediction Of Disease Progressmentioning
confidence: 99%
“…In a chickpea field at Poggiorsini (40 • 54 N 16 The model was operated starting from the day of the last assessment in which no disease was observed. Both predicted infection severity and observed disease severity were accumulated during each disease assessment period and were rescaled to their final value; values were rescaled from 0 to 1 to make the data collected in different experiments comparable [76,77]. For the evaluation of model performance, the root mean square error (RMSE), the coefficient of residual mass (CRM), and the concordance correlation coefficient (CCC) were calculated [78,79].…”
Section: Disease Progressmentioning
confidence: 99%